1982
DOI: 10.1017/s0022112082001499
|View full text |Cite
|
Sign up to set email alerts
|

Concentration fluctuations and fluxes in plumes from point sources in a turbulent boundary layer

Abstract: Measurements have been made of concentration fluctuations and turbulent fluxes for two passive plumes from an elevated and a ground-level source in a turbulent boundary layer. For the concentration fluctuations, results are presented for the variance, the intermittency, peak values of concentration, probability-density functions and spectra. The balance of terms in the variance transport equation is examined, as is the overall level of fluctuations along the plume. It is shown that most of the production of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
294
4
3

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(366 citation statements)
references
References 6 publications
65
294
4
3
Order By: Relevance
“…The dispersion of ground level and elevated scalar releases has also been studied in wind tunnels over a rough bed (6,7). A summary of the findings from these studies is given in Rahman and Webster (5).…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion of ground level and elevated scalar releases has also been studied in wind tunnels over a rough bed (6,7). A summary of the findings from these studies is given in Rahman and Webster (5).…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out by Fackrell and Robins (1982), the advection terms and the diffusion terms are quite large close to the source (for a neutral boundary layer up to three times the boundary height). They also found that the two terms are almost equal but with opposite sign.…”
Section: (B) Only Advection Experiments (Oadv)mentioning
confidence: 81%
“…According to measurements by Fackrell and Robins (1982) in a neutral boundary layer these terms are as important as other terms close to the source (three times the boundary-layer height). Therefore, in the present model the terms are retained and the consequence of neglecting any of the terms will be discussed in the sensitivity tests.…”
Section: The Basic Model Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This example [9] is perhaps one of the best with which to illustrate how wind tunnel experiments can stimulate modelling developments. The research arose because of a need to model short duration emissions from nuclear power plant-this prompted development of the experimental techniques [7] and triggered the basic research, undertaken both to provide a reference framework and because of its inherent interest.…”
Section: Concentration Fluctuationsmentioning
confidence: 99%